And the bicentennial arrived! City, social class and housing in Lima (1821-2020) - Calderón Cockburn, Julio (2020)
This article attempts a balance of the city of Lima in its pattern of spatial growth and attention to the housing problem during the republican period (1821-2020), paying attention to the process of inequality generated according to the various social classes. Addresses three periods: 1821-1920, characterized by the predominance of the free market in housing production, 1921-1989 in which the axes of the of the city are defined, the patterns of social and spatial segregation are established and the approaches of modern urbanism give way to a “realistic” vision that accepts the “barriadas” (slums) as the “solution” to housing. Finally, the period 1990-2020, represents the adoption of neoliberal policies and a relative abandonment of the role of the State, with consequences of the greater promotion of informality and the worsening of housing care.